Discovery of conformation constrained tetracyclic compounds as potent chitinase OfChi-h inhibitors with a novel binding mode - Pengtao Yuan; Xi Jiang; Xintong Ni; Xusheng Shao; Xuhong Qian; Qing Yang (Journal of Enzyme Inhibition and Medicinal Chemistry)
Chitinase h (Chi-h) has been identified as a promising pesticide target due to its exclusive distribution in lepidopteran insects and its essential role in the moulting processes. In this study, we leverage OfChi-h from destructive agricultural pest Ostrinia furnacalis (Asian corn borer) as a model target to identify novel chitinase inhibitors. A conformational restriction approach was employed to design a series of novel OfChi-h inhibitors. Among these, compound 6a showed the highest inhibitory activity against OfChi-h, with a Ki value of 58 nM. Molecular docking analysis suggested that 6a tightly bound to three subsites (-3 to −1) of OfChi-h. The binding mode is further confirmed by the co-crystallization data of 6a with the SmChiA, a bacterial homologue of OfChi-h, at a resolution of 1.8 Å. This research presents a novel approach for the development of highly potent insect chitinase inhibitors, offering potential tools for effective pest control.